Sosialisasi Penggunaan Aplikasi Siap Terbang dalam Penanganan Cargo Udara - Sari, Mustika; Perawati, Duyesna; Mafrudoh, Lut (Jurnal Abdimas Transportasi & Logistik, 2024)
This outreach activity aims to introduce and increase understanding of air cargo service users, especially employees of PT. Precision Logistics International, regarding the Ready to Fly Application launched by the Directorate General of Customs and Excise. This application is designed to simplify the process of processing export-import cargo documents at Soekarno-Hatta Airport, especially in the context of digitalization and the COVID-19 pandemic, which requires reducing physical interaction and implementing an online system. The outreach methods used include live and interactive demonstrations, which make it easier for participants to understand and operate the main features of the application, such as submitting documents and checking application status. The results of this activity show participant enthusiasm and increased efficiency in work processes, which has the potential to reduce cargo handling time and storage costs. With this outreach, it is hoped that service users can work more effectively, improve service quality, and support the company's smooth operations.